Perceptions of Peer Support for Victim-Survivors of Sexual Violence and Abuse: An Exploratory Study With Key Stakeholders. Issue 15 (August 2022) - Gregory, Alison; Johnson, Emma; Feder, Gene; Campbell, John; Konya, Judit; Perôt, Concetta
Experiences of sexual violence, childhood sexual abuse, and sexual assault are common across all societies. These experiences damage physical and mental health, coping ability, and relationships with others. Given the breadth and magnitude of impacts, it is imperative that there are effective, accessible services to support victim-survivors, ease suffering, and empower people to cope, recover and thrive. Service provision for this population in the United Kingdom is complex and has been hit substantially by austerity. Since positive social support can buffer against negative impacts, peer support may be an effective approach. The aim of this exploratory study was to capture the views and perspectives of professional stakeholders concerning service provision for victim-survivors, particularly perceptions of peer support. In-depth semistructured interviews were conducted in the UK during 2018 with six professional stakeholders, highly experienced in the field of service provision for victim-survivors of sexual violence and abuse. An abductive approach to analysis was used, applying principles from thematic analysis. Our sample comprised four females and two males, and their roles included psychiatrist, general practitioner, service improvement facilitator, and senior positions within victim-survivor organizations. Interviews highlighted models of peer support for this population, good practice and safety considerations, and a lack of uniformity regarding quality and governance standards across the sector. Findings indicated that current funding models impact negatively on victim-survivor services, and that provision is fragmented and insufficient across statutory and not-for-profit sectors. The influence of the medical model upon service provision was evident, which resulted in apprehension around support delivered in less-usual forms—including peer support. Further research is needed to explore the potential of peer support for victim-survivors of sexual violence and abuse.